A probe into the artistic techniques of play-within-a-play in Jiang Shiquan’s dramas - Gao, Yuan (2023)
As a traditional method of drama creation, "play-within-a-play" can create a faint foreshadowing, exquisite and fascinating drama effect, which is used by many dramatists. As a famous dramatist in the middle of Qing Dynasty, Jiang Shiquan was also expert in using this artistic technique in his dramatic works. The purpose of this thesis is to explore the narrative art and creative principles of Jiang Shiquan's "play-within-a-play" technique in his dramatic works. Jiang Shiquan (1725-1785) is one of the famous dramatists in the history of the legendary development of Kunshan accent in the Qing Dynasty. His drama creations began in the 16th year of Qianlong (1751) and ended in the 46th year of Qianlong (1781). Lots of literati and scholars in ancient times have made extremely high evaluations of his operas. However, what is not commensurate with Jiang Shiquan’s literary achievements and status is that since 1949, the research on Jiang Shiquan’s literary creations has been very weak, and there has been a bias in interpretation. Therefore, this thesis intends to make an objective evaluation of Jiang Shiquan's works through the study of the "play- within-a-play" technique. The research scope of the thesis covers the sixteen existing dramas of Jiang Shiquan, including the Nine Chinese Opera Anthology of Cang Yuan, which has been extensively studied by scholars, as well as Lushan Meeting, Picture of Caiqiao and Caishiji three types and Xijiang Zhugu four species. The thesis will summarize the arrangement of the "play-within-a-play" technique of different types of internal dramas in dramas which were created by Jiang Shiquan and focus on the interspersed mode of internal dramas in Jiang Shiquan's "play- within-a-play" technique, analyze and explore the different characteristics and functions embodied in different interspersed modes. On the basis of his 16 existing dramas, the thesis will analyze the role of his “play-within-a-play” technique and explores the narrative art of his works. Based on Jiang Shiquan's plays, this dissertation comprehensively analyzes the “play-within-a-play” technique through comprehensive literature research, interdisciplinary research and comparative research, and strives to gain an in- depth understanding of Jiang Shiquan's creative ideas, opera structure and historical value through a comprehensive analysis of the "play-within-a-play" technique, which provides a new perspective for examining Jiang Shiquan's opera creation and brings new vitality to the classical opera creation and research.